SPME-GC–MS combined with chemometrics to assess the impact of fermentation time on the components, flavor, and function of Laoxianghuang - Yaqun, Liu; Hanxu, Liu; Wanling, Lin; Yingzhu, Xue; Mouquan, Liu; Yuzhong, Zheng; Lei, Hu; Yingkai, Yang; Yidong, Chen (Frontiers in Nutrition, 2022)
Laoxianghuang, fermented from Citrus medica L. Var. Sarcodactylis Swingle of the Rutaceae family, is a medicinal food. The volatiles of Laoxianghuang fermented in different years were analyzed by solid-phase microextraction combined with gas chromatography-mass spectrometry (SPME-GC-MS). Meanwhile, the evolution of its component-flavor-function during fermentation process was explored in depth by combining chemometrics with multiple perspectives. A 65 μm PDMS/DVB fiber, extraction time of 30 min and desorption temperature of 200 oC were used as the optimal conditions. 42, 44, 52, 53, 53 and 52 volatiles were identified in the 3rd, 5th, 8th, 10th, 15th and 20th years of fermentation of Laoxianghuang with relative contents of 97.87%, 98.50%, 98.77%, 98.85%, 99.08% and 98.36%, respectively. Terpenes displayed the highest relative content and were positively correlated with the year of fermentation, followed by alcohols, ketones, aldehydes, phenols, esters and ethers. PCA and HCA analyses showed a closer relationship between the composition of Laoxianghuang with similar fermentation years of the same gradient (3rd-5th, 8th-10th, 15th-20th). PLS-DA VIP scores and PCA-bioplot showed that α-terpineol, γ-terpinene, cymene, limonene and terpinolene were the differential candidate biomarkers. Flavor analysis revealed that Laoxianghuang exhibited wood odor from the 3rd to the 10th year of fermentation, while herb odor appeared in the 15th and the 20th year. In addition, Laoxianghuang possessed biological activity related to digestive system diseases and cancer throughout the fermentation process, and developed effects associated with obesity, hypertension and diabetes after the 8th year of fermentation. This study analyzed the change pattern of flavor and function of Laoxianghuang through the evolution of the composition, which provided a theoretical basis for further research on subsequent fermentation.